Postseismic deformation following the 2 July 2013 Mw 6.1 Aceh, Indonesia, earthquake estimated using GPS data. (15th June 2019) - Gunawan, Endra; Widiyantoro, Sri; Zulfakriza,; Meilano, Irwan; Pratama, Cecep
Graphical abstract: Highlights: The ongoing postseismic deformation of the 2004 Mw 9.2 Sumatra-Andaman earthquake. The ongoing postseismic deformation of the 2012 Mw 8.6 Indian Ocean earthquake. No poroelastic rebound after the 2 July 2013 Mw 6.1 Aceh earthquake. No viscoelastic relaxation after the 2 July 2013 Mw 6.1 Aceh earthquake. Afterslip after the 2 July 2013 Mw 6.1 Aceh earthquake occurred at two different fault segments. Abstract: GPS data after the 2 July 2013 Mw 6.1 Aceh earthquake provide valuable information for understanding the postseismic behavior of a strike-slip fault in northern Sumatra, Indonesia. The analysis of postseismic deformation following the 2004 Sumatra-Andaman earthquake and the 2012 Indian Ocean earthquake suggest that the ongoing deformation affected northern Sumatra between July and December 2013. The postseismic deformation of the 2013 Aceh earthquake is herein investigated, with the contribution of poroelastic rebound and viscoelastic relaxation evaluated. The results suggest that the model displacement of those two mechanisms failed to estimate the data. The afterslip analysis of the 2013 Aceh earthquake, on the contrary, fits the data very well with a seismic slip occurring at multiple fault segments of the Sumatran fault in northern Sumatra, Indonesia.